Reduction of Toluidine Blue by Sulfur(IV) in Acetate Buffer Medium: Kinetics and Mechanism - K. Sen, Pratik; N. Bera, Rabindra; Pal, Biswajit (Asian Journal of Chemistry, 2015)
The reduction of toluidine blue (TB+) by sulfite [S(IV)] was studied spectrophtometrically in acetic acid-sodium acetate buffer medium in the temperature range 293-308 K. The reaction showed first order dependence on toluidine blue. The reaction was found to be first order in S(IV) at lower substrate concentration ([S(IV)] £ 0.07 mol dm-3) but the reaction became second order in S(IV) at high substrate concentration ([S(IV)] > 0.07 mol dm-3). H+ ions were found to inhibit the reaction in the pH range 4.0-5.4. The rate decreased with increase in the ionic strength of the medium, but remained unchanged with decreasing dielectric constant of the medium. The oxidation reaction possibly involved a one-electron transfer step via a free radical mechanism. An overall enthalpy and entropy of activation were computed. A plausible mechanism and rate law corroborating the experimental results have been put forward.